Soil Hydrological Attributes of an Integrated Crop-Livestock Agroecosystem: Increased Adaptation through Resistance to Soil Change - Mark A. Liebig; Don L. Tanaka; Scott L. Kronberg; Eric J. Scholljegerdes; Jim F. Karn (Applied and Environmental Soil Science)
Integrated crop-livestock systems have been purported to have significant agronomic and environmental benefits compared to specialized, single-enterprise production systems. However, concerns exist regarding the effect of livestock in integrated systems to cause soil compaction, thereby decreasing infiltration of water into soil. Such concerns are compounded by projections of more frequent high-intensity rainfall events from anticipated climate change, which would act to increase surface runoff and soil erosion. A study was conducted to evaluate the effects of residue management, frequency of hoof traffic, season, and production system (e.g., integrated annual cropping versus perennial grass) on infiltration rates from 2001 through 2008 in central North Dakota, USA. Imposed treatments had no effect on infiltration rate at three, six, and nine years after study establishment, implying that agricultural producers should not be concerned with inhibited infiltration in integrated annual cropping systems, where winter grazing is used. The use of no-till management, coupled with annual freeze/thaw and wet/dry cycles, likely conferred an inherent resistance to change in near-surface soil properties affecting soil hydrological attributes. Accordingly, caution should be exercised in applying these results to other regions or management systems.